2021
DOI: 10.3390/informatics8020024
|View full text |Cite
|
Sign up to set email alerts
|

Acceptance of Google Meet during the Spread of Coronavirus by Arab University Students

Abstract: The COVID-19 pandemic not only affected our health and medical systems but also has created large disruption of education systems at school and universities levels. According to the United Nation’s report, COVID-19 has influenced more than 1.6 billion learners from all over the world (190 countries or more). To tackle this problem, universities and colleges have implemented various technologically based platforms to replace the physical classrooms during the spread of Coronavirus. The effectiveness of these te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
45
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(52 citation statements)
references
References 62 publications
4
45
0
3
Order By: Relevance
“…Regarding the degree of satisfaction of the participants with the use of the audiovisual telecommunications platform in teaching, it was found to be moderate, with the nursing students expressing a higher degree of satisfaction, followed by the physiotherapy students; on the other hand, the podiatry students expressed a lower degree of satisfaction. Previous studies carried out in circumstances of home isolation obtained a similar or even higher degree of satisfaction than in the present investigation, as they perceived ease of use due to its simple operation and the advantages offered by this platform [12,25]. However, it should be borne in mind that face-to-face teaching improves interpersonal communication, facilitating the establishment of group dynamics.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Regarding the degree of satisfaction of the participants with the use of the audiovisual telecommunications platform in teaching, it was found to be moderate, with the nursing students expressing a higher degree of satisfaction, followed by the physiotherapy students; on the other hand, the podiatry students expressed a lower degree of satisfaction. Previous studies carried out in circumstances of home isolation obtained a similar or even higher degree of satisfaction than in the present investigation, as they perceived ease of use due to its simple operation and the advantages offered by this platform [12,25]. However, it should be borne in mind that face-to-face teaching improves interpersonal communication, facilitating the establishment of group dynamics.…”
Section: Discussionsupporting
confidence: 65%
“…In other words, pairs of students have been defined, who would share experiences and learning throughout all the practical classes of the entire course [ 11 ]. Owing to the advantages of digital tools, such as the fact that commuting is no longer needed, allowing social distance and flexibility in time, they have been maintained in this academic year, combined with face-to-face teaching, to facilitate the delivery of virtual teaching by teachers and/or the virtual attendance of students to theoretical classes [ 12 ]. This distance modality is of special interest in those cases of home isolation for being COVID-19 positive or for being in direct contact with someone who has tested positive, having to keep the quarantine at home to preserve the health of other people [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Researchers can adapt and/or adopt questionnaire that was constructed by Venkatesh and Bala (2008) that helps to gauge the level of knowledge and awareness of ESL primary school teachers in integrating 4IR into their teaching practices. Researchers may also adapt or adopt questionnaires constructed by Al-Maroof et al (2021) that help to investigate students' acceptance of technologies since acceptance is associated to the level of readiness in integrating 4IR as part of classroom activities. All the data collected using quantitative instruments can be triangulated using qualitative instruments such observation, interviews and open-ended questions to gather more established findings.…”
Section: Research Design and Ethicsmentioning
confidence: 99%
“…Thus, it is not surprising to see how 4IR has caused a gradual shift from traditional teaching to digital teaching. Many teaching theories and research findings indicated an enhanced teaching quality when it is facilitated by digital teaching (Al-Maroof et al, 2021;Van et al, 2021;Lawrence et al, 2019;Hashim et al, 2019;Mofareh, 2019;Ahmadi, 2018;Xu et al, 2018;Yunus, 2018), which also affects learning outcomes (Quarles et al, 2018). Fisk (as cited in Anaelka, 2018) also stated that with the new vision of learning, pupils are not only promoted as learners who learn necessary skills and knowledge, but they are also responsible to identify sources that enable their learning these skills and knowledge.…”
Section: Introductionmentioning
confidence: 99%
“…The survey of Bui et al, [12] presented the behavioural intention of Vietnamese female students (N=254) to use video conferencing tools (VCTs; e.g., Zoom, Microsoft Teams, or Google Hangout) in the COVID-19 pandemic. Similarly, Al-Maroof et al, [13] attempted to explore the effect of Google Meet acceptance among Arab students (N=475) during the pandemic in Oman, UAE, and Jordan.…”
Section: The Literature Reviewmentioning
confidence: 99%